Evaluation of Possible Toxic Effects of Thymus vulgaris leave Extract on Thyroid Function and Fertility in Male Rats - Noori Mohammed Luaibi (Journal of Global Pharma Technology, 2017)
Thyme has been used for thousands of years for a myriad of indications. This experiment was conducted to evaluate the effects of thyme leave extracts on some rat organs and hormones such as TSH, T3, T4 and Testosterone after serial period times of injection with different concentrations. 75 Spargue-Dawley albino adult male rats were randomly distributed into five groups of control and treated groups. Each group had 15 rats, group1 for the negative control, group 2 for the positive control, group 3, 4, and 5 were treated with thyme in the concentration of (500, 750and1000) mg/kg of body weight by injection for 10,20, and 30 days subsequently. According to statistical analysis revealed that the level of T3, T4 and testosterone were decreased in treated groups in comparison with control groups and the decreasing value of these hormones were continuing to occur in high concentrations with long period of time injecting with thyme leave extract, While the level of TSH illustrated increment in high concentrations and long periods of time exposing to thyme leaves extract.Keywords: TSH, T3, T4 ,Testosterone, Thymus vulgaris.